رضا الزبون؛ كمؤشر للخدمة الفندقية – دراسة ميدانية بفنادق ولاية تيارت المدينة- - منور, ماريف (جامعة الوادي - University of Eloued, 2021)
تهدف هذه الدراسة إلى الكشف عن مستويات كل من رضا الزبون والخدمة الفندقية، وعن مدى وجود علاقة ارتباطية بينهما، وعن الفروق في مستوى رضا الزبون بدلالة كل من المستوى التعليمي والوظيفة. تم اعتماد المنهج الوصفي التحليلي، وعلى الاستبيان كأداة لجمع المعلومات المتعلقة بمتغيري رضا الزبون والخدمة الفندقية. تم إجراء الدراسة على عينة قوامها أربع وستون (64) زبونا وافدا على الفنادق المقصودة بالدراسة، وذلك بعد التأكد من الخصائص السيكومترية لأدوات القياس. أسفرت نتائج الدراسة عن مستويات متوسطة لكل من رضا الزبون والخدمة الفندقية، وعن وجود علاقة ارتباطية دالة إحصائيا بينهما، وأيضا علاقة ارتباطية دالة إحصائيا بين رضا الزبون وكل من الخدمة المادية والخدمة المعنوية، وانعدام فروق دالة إحصائيا في رضا الزبون بدلالة كل من المستوى التعليمي، ومع وجود فروق دالة إحصائيا في رضا الزبون تُعزى لمتغير وظيفة زبون. This study aims to reveal the levels of both customer satisfaction and hotel service, the extent of a correlational relationship between them, and the differences in the level of customer satisfaction in terms of educational level and job. The descriptive and analytical approach was adopted, and the questionnaire was used as a tool to collect information related to the two variables of customer satisfaction and hotel service. The study was conducted on a sample of sixty-four (64) clients coming to the hotels intended for the study, after verifying the psychometric properties of the measuring instruments. The results of the research resulted in average levels for both customer satisfaction and hotel service, the existence of a statistically significant correlation between them, and also a statistically significant correlation relationship between customer satisfaction and both material and moral service, and the absence of statistically significant differences in customer satisfaction in terms of both educational level, and with There are statistically significant differences in customer satisfaction due to a customer job variable.
Customer satisfaction; As an indicator of hotel service - A field study in the hotels of the state of Tiaret, the city -
Keywords: خدمة فندقية ; خدمة مادية ; رضا